2011
DOI: 10.1159/000321900
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a New Compact Male Intermittent Catheter: Randomized, Cross-Over, Single-Blind Study in Healthy Male Volunteers

Abstract: Introduction: A new compact male intermittent catheter was compared with a regular intermittent male catheter in terms of safety and acceptability. Methods: In this randomized, single-blind, cross-over study, healthy male volunteers were catheterized twice with a compact catheter and twice with a regular catheter. Results: 28 participants were enrolled. Mean ± SD discomfort (visual analogue scale; primary objective) was 2.25 ± 1.5 and 2.52 ± 1.8 for the compact and regular catheters, respectively (difference –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although it is a subjective measure, it has been used successfully in other clinical trials comparing catheters. 12,14 The non-inferiority demonstrated in this trial is therefore a key clinically relevant result, together with the lack of any additional pain, resistance or stinging. This is important, as other results described here suggest that the compact catheter may have other advantages over the standard catheter.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although it is a subjective measure, it has been used successfully in other clinical trials comparing catheters. 12,14 The non-inferiority demonstrated in this trial is therefore a key clinically relevant result, together with the lack of any additional pain, resistance or stinging. This is important, as other results described here suggest that the compact catheter may have other advantages over the standard catheter.…”
Section: Discussionmentioning
confidence: 71%
“…12,15 In particular, a study in healthy volunteers by Bagi et al 12 comparing standard and compact catheters has shown no difference in discomfort, stinging or pain between the two catheters. Another study in women with a similar compact catheter also found that it was at least as efficient at emptying the bladder as more conventional female catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean discomfort ratings were generally low for all participants (<2.5 cm) and independent of catheter type. In the literature, the mean or median VAS scoring is generally in the 0-to 3-cm range [32][33][34][35] where previous IC experience, pain anticipation, and type of catheter (coated vs uncoated) are some factors that seem to affect VAS discomfort ratings. Therefore, higher discomfort rating in HV compared to IC users in the current studies was expected and correlates with a study by Girotti and colleagues 36 where adjustment to IC affected the mean VAS scoring scale for discomfort over time from 3.7 cm at 3 months to 2.5 cm at 6 months was reported.…”
Section: Discussionmentioning
confidence: 99%